The blood of lambs : a former terrorist's memoir of death and redemption - Vincent, Lynn. (West Monroe, LA : Howard Books, 2009)
A former member of the Islamic jihad recounts his early life in a terror training camp, his travels through the Middle East pursuing Umma, his conversion to Christianity, and his thoughts on the dangers of radical Islam
Keywords: Saleem, Kamal,1958-; Child terrorists -- Middle East -- Biography; Christian converts from Islam -- United States -- Biography